2019
DOI: 10.1186/s12974-019-1635-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of soluble epoxide hydrolase delays the progression of Alzheimer’s disease

Abstract: BackgroundSoluble epoxide hydrolase (sEH) is a bifunctional enzyme with COOH-terminal hydrolase and NH2-terminal lipid phosphatase activities. It is expressed in various cell types in the brain and is involved in the pathogenesis of inflammatory and neurodegenerative diseases. Alzheimer’s disease (AD) is a progressive neuroinflammatory and neurodegenerative disease. However, the pathological significance of sEH and underlying molecular mechanism in AD remain unclear.MethodsTo examine the role of sEH in pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
106
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(118 citation statements)
references
References 52 publications
12
106
0
Order By: Relevance
“…2B). We observed elevated expression of sEH predominantly in GFAP-positive astrocytes in Tg samples, with negligible co-staining with Iba1, consistent with previous findings (27). Both the sEH fluorescence intensity and the number of sEH expressing cells were increased significantly in Tg mice compared to N-Tg controls ( Fig.…”
Section: Tppu Blocks Astroglial Seh Upregulation and Lps-induced Inflsupporting
confidence: 91%
See 2 more Smart Citations
“…2B). We observed elevated expression of sEH predominantly in GFAP-positive astrocytes in Tg samples, with negligible co-staining with Iba1, consistent with previous findings (27). Both the sEH fluorescence intensity and the number of sEH expressing cells were increased significantly in Tg mice compared to N-Tg controls ( Fig.…”
Section: Tppu Blocks Astroglial Seh Upregulation and Lps-induced Inflsupporting
confidence: 91%
“…However, they are broken down rapidly into their corresponding diols by the soluble epoxide hydrolase (sEH). Genetic deletion of Ephx2 (gene encoding sEH) or pharmacological inhibition of sEH conferred beneficial effects in several disease models, including depression, Parkinson's disease (23)(24)(25)(26), and most recently, APP/PS1 transgenic mouse model of AD (27). However, these studies are restricted to acute model systems or germline deletions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, sEHi impacted on AD hallmarks as amyloid plaques and tau hyperphosphorylation, preventing cognitive decline after oral administration [110]. Additionally, Lee et al (2019) [111] demonstrated that sEH deletion in an AD mice model (APP/PS1) reduced and delayed the development of cognitive impairment and specific markers of the disease such as β-amyloid deposition and apoE expression.…”
Section: Soluble Epoxide Hydrolase In Central Nervous System Disordersmentioning
confidence: 99%
“…sEH could likely represent a promising therapeutic target for neurological disorders such as depression, PD, LBD, and AD [108,110,111,147]. In the recent past, several reports demonstrated the usefulness of small molecules for inhibiting sEH activity, which was effective against several illness conditions such as cancer, hypertension, heart diseases (ischemia, cardiac, and renocardiac failures), obesity, and diabetic neuropathy [148][149][150][151][152][153][154][155][156].…”
Section: Therapeutic Use Of Seh Modulation In Parkinson's Diseasementioning
confidence: 99%